Analysis of Costs and Return of Groundnut Production (Arachis hypogaea L.) on Household Poverty Alleviation in Southern Part of Taraba State, Nigeria - K, Istifanus T.; O, Egbeadumah M.; G, Bulus (Darul Yasin Al Sys, 2025)
This study analyzed the costs and returns associated with groundnut production in the southern part of Taraba State, Nigeria, with the aim of assessing its profitability and identifying production constraints. Data were collected from 177 groundnut farmers using structured questionnaires. Analytical methods included descriptive statistics and gross margin analysis. The results revealed that 66.7% of respondents were male, with a mean age of 41 years, and 58.8% possessed tertiary education. Most farmers (66.1%) had over 10 years of farming experience, and 79.7% cultivated less than 3 hectares of land. Groundnut production was found to be profitable, generating an average gross revenue of ₦248,786.00 and a gross margin of ₦159,865.62 per hectare. The major variable costs were attributed to seeds (29%), transportation (24%), herbicides (19%), labor (14%), fertilizer (10%), and miscellaneous expenses (5%). Key production challenges identified included high interest rates (85.9%), climate change (75.1%), and rising production costs (67.8%). The study concludes that groundnut farming in the region is economically viable. It recommends that the government subsidize critical inputs such as seeds and herbicides, and invest in improved storage infrastructure to reduce post-harvest losses and enhance profitability for smallholder farmers.